Satellyptus: analysis and database of microsatellites from ESTs of Eucalyptus - Ceresini, Paulo Cezar [UNESP]; Silva, Cristina Lacerda Soares Petrarolha [UNESP]; Missio, Robson Fernando [UNESP]; Souza, Elaine Costa [UNESP]; Fischer, Carlos Norberto [UNESP]; Guillherme, Ivan Rizzo [UNESP]; Gregorio, Ivo [UNESP]; Silva, Eloiza Helena Tajara da [UNESP]; Cicarelli, Regina Maria Barreto [UNESP]; Silva, Marco Túlio Alves da [UNESP]; Garcia, José Fernando [UNESP]; Avelar, Gustavo Arbex [UNESP]; et al. (Sociedade Brasileira de Genética, 2005)
The main goal of our research was to search for SSRs in the Eucalyptus EST FORESTs database (using a software for mining SSR-motifs). With this objective, we created a database for cataloging Eucalyptus EST-derived SSRs, and developed a bioinformatics tool, named Satellyptus, for finding and analyzing microsatellites in the Eucalyptus EST database. The search for microsatellites in the FORESTs database containing 71,115 Eucalyptus EST sequences (52.09 Mb) revealed 20,530 SSRs in 15,621 ESTs. The SSR abundance detected on the Eucalyptus ESTs database (29% or one microsatellite every four sequences) is considered very high for plants. Amongst the categories of SSR motifs, the dimeric (37%) and trimeric ones (33%) predominated. The AG/CT motif was the most frequent (35.15%) followed by the trimeric CCG/CGG (12.81%). From a random sample of 1,217 sequences, 343 microsatellites in 265 SSR-containing sequences were identified. Approximately 48% of these ESTs containing microsatellites were homologous to proteins with known biological function. Most of the microsatellites detected in Eucalyptus ESTs were positioned at either the 5 or 3 end. Our next priority involves the design of flanking primers for codominant SSR loci, which could lead to the development of a set of microsatellite-based markers suitable for marker-assisted Eucalyptus breeding programs.
Keywords: bioinformatics tool; genetic markers; gene ontology; small sequence repeats; SSR